2017
DOI: 10.3892/ol.2017.5803
|View full text |Cite
|
Sign up to set email alerts
|

Increased Six1 expression is associated with poor prognosis in patients with osteosarcoma

Abstract: Sine oculis homeobox homolog 1 (Six1) is an evolutionarily conserved transcription factor that acts as master regulator of development and is frequently dysregulated in various types of cancer. Six1 has been demonstrated to be upregulated in human osteosarcoma cell lines compared with osteoblastic cell lines. However, the association of Six1 expression with the progression and prognosis of osteosarcoma patients remains unclear. The purpose of the present study was to investigate the association between Six1 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…3 Additionally, increased SIX1 level is associated with poor survival outcome of osteosarcoma patients. 4 However, the biological function of SIX1 in HCC is rarely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…3 Additionally, increased SIX1 level is associated with poor survival outcome of osteosarcoma patients. 4 However, the biological function of SIX1 in HCC is rarely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…22 Moreover, multiple studies have demonstrated that high SIX1 expression leads to poor survival in a variety of cancers. [23][24][25] In our concurrent study, in cultured melanoma cells, SIX1 was proven to promote cell proliferation and invasion, and SIX1 expression could be inhibited by miR-150-5p, which exhibited inhibitory functions in melanoma cell. 26 However, the in vivo metastatic functions and the clinical significance of SIX1 in melanoma are unknown.…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies have shown that SIX1 expression is correlated with the prognosis of multiple types of cancer (26,27). Therefore, the present study investigated SIX1 expression in NSCLC tissues.…”
Section: Six1 Expression Is Upregulated In Nsclc Tissues and Correlat...mentioning
confidence: 99%